Mineral-based reservoir diaphragm wall reinforcing and curing agent as well as preparation method and application thereof
By using mineral-based reservoir anti-seepage wall reinforcement and curing agent, the problem of high energy consumption and unsatisfactory curing effect of existing reinforcement materials is solved, and the density and durability are achieved, and the service life of the reservoir anti-seepage wall is extended.
Patent Information
- Application Number
- CN202411950756.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing reservoir anti-seepage wall reinforcement materials have problems such as high energy consumption, environmental pollution and poor curing effects in production and application, resulting in poor anti-seepage effect and short service life.
A mineral-based reservoir anti-seepage wall reinforcement and curing agent is used, which consists of cement, modified composite powder, polyacrylamide and sodium polyacrylate. Through the preparation method of modified composite powder, a flocculation structure and a crosslinked structure are formed to improve the density and durability of the cured body.
It improves the density and durability of the cured body, reduces moisture penetration, extends the service life of the reservoir's anti-seepage wall, and reduces energy consumption and environmental pollution in the production process.
Smart Images

Figure BDA0005214812470000071
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of hydraulic structure repair, and in particular to a mineral-based reservoir anti-seepage wall reinforcement and curing agent, and a preparation method and application thereof. Background Art
[0002] As an important water conservancy facility, reservoirs play a key role in flood control, irrigation, water supply, etc. The maintenance of reservoir anti-seepage walls is an important part of ensuring the safe operation of reservoirs.
[0003] At present, the reinforcement of reservoir anti-seepage walls mainly relies on cement-based reinforcement materials. However, the existing cement-based reinforcement materials require high-temperature calcination during the production process, which consumes a lot of energy and resources, and releases a large amount of carbon dioxide, which has an adverse impact on the environment. In addition, the curing effect of cement-based reinforcement materials in actual applications is not ideal, and it is difficult to quickly form a high-strength, low-permeability stable layer, resulting in poor anti-seepage effect and may cause new cracks, affecting the safety and service life of the reservoir. Summary of the invention
[0004] In order to improve the density and durability of the cured material, effectively reduce water penetration, and extend the service life of the reservoir anti-seepage wall, the present application provides a mineral-based reservoir anti-seepage wall reinforcement curing agent and its preparation method and application.
[0005] In the first aspect, the present application provides a mineral-based reservoir anti-seepage wall reinforcement curing agent, which adopts the following technical scheme: a mineral-based reservoir anti-seepage wall reinforcement curing agent, which is prepared by weight from the following raw materials: 18-22 parts of cement, 50-65 parts of modified composite powder, 11-13 parts of polyacrylamide, and 3.5-5.5 parts of sodium polyacrylate; the raw materials for preparing the modified composite powder include composite powder, aminosilane and fumaric acid, and the weight ratio of the composite powder, aminosilane and fumaric acid is 10:(1.2-1.6):(3.5-4.5).
[0006] By adopting the above technical scheme, the composite powder and cement are easy to form a flocculated structure after adding water. After modification, the composite powder is evenly dispersed in the cement and polymer system, and forms a good particle gradation with cement, effectively filling the pores of the solidified body, and the CSH gel generated later will further refine the capillary pores of the cement stone, improve the density of the solidified body, and effectively improve the soil binding ability, thereby improving the strength and durability of the solidified body, reducing water penetration, and extending the service life of the solidified body. Among them, the alkoxy group in the aminosilane will generate active silanol after hydrolysis, and the silanol and the hydroxyl group on the surface of the composite powder will undergo a condensation reaction to form a chemical bond, and the amino group will react with fumaric acid to form a cross-linked structure. At the same time, fumaric acid and polyacrylamide produce staggered polymer molecules, which improves the curing performance of the curing agent. In addition, sodium polyacrylate absorbs a large amount of free water and stores it in molecular chain microunits, which not only reduces the penetration of water in the solidified soil but also improves the density.
[0007] Preferably, the composite powder comprises granulated blast furnace slag powder, fly ash and ceramic powder, and the weight ratio of the granulated blast furnace slag powder, fly ash and ceramic powder is 1:(0.2-0.4):(0.5-0.7).
[0008] By adopting the above technical solution, compared with single mineral powder, by compounding granulated blast furnace slag powder, fly ash and ceramic powder, the shortcomings of single mineral powder can be made up, and the superposition effect of multiple materials can be brought into play, filling the gaps between cement particles, reducing porosity and forming a denser structure. In addition, the composite powder increases the dissolution of active oxides such as active SiO2 and Al2O3, increases the contact area of the volcanic ash effect reaction, greatly advances the secondary hydration reaction time of the composite powder, and improves the early and late strength and durability of cement.
[0009] Preferably, the preparation method of the modified composite powder is: (1) granulated blast furnace slag powder, fly ash and ceramic powder are uniformly mixed and ball milled for 2-3 hours to obtain a composite powder, and then the composite powder is added to a NaOH solution, rapidly stirred and fully dispersed for 1-2 hours, filtered and dried to obtain a pretreated powder; (2) adding aminosilane to a dispersant to obtain a modified liquid; fully dispersing the pretreated powder in the dispersant to obtain a suspension; introducing nitrogen to uniformly mix the modified liquid and the suspension, reacting under mechanical stirring at 60-70° C. for 2-4 hours, filtering, washing with anhydrous ethanol, and drying to obtain a silanized powder; (3) dissolving fumaric acid in an ethanol solution, then adding the silanized powder to the fumaric acid solution, reacting for 3-5 hours under mechanical stirring at 75-85° C., washing with anhydrous ethanol for 2-3 times, filtering and drying to obtain a modified composite powder.
[0010] Preferably, the dispersant in step (2) is N-methylpyrrolidone.
[0011] By adopting the above technical scheme, the composite powder is hydroxylated by using NaOH solution to increase the number of hydroxyl groups on the surface of the composite powder, thereby improving the reaction activity of the composite powder; the hydroxylated powder is then silanized by aminosilane, and finally the powder is amidated by fumaric acid, thereby effectively increasing the compatibility of the composite powder between cement and polymer materials, and the composite powder is evenly dispersed in the composite material system, effectively reducing the stacking porosity of the powder, and forming a high-density, low-permeability reinforcement layer in the solidified soil.
[0012] Preferably, the aminosilane is one or more of 3-aminopropyltriethoxysilane, N-2-aminoethyl-3-aminopropyltrimethoxysilane, and 3-diethylenetriaminopropyltrimethoxysilane.
[0013] By adopting the above technical solution, aminosilane combines with the hydroxyl group on the surface of the composite powder through the silanol group, and the amine group undergoes a dehydration reaction with the carboxyl group in fumaric acid, so that aminosilane and fumaric acid are successfully coated on the surface of the composite powder as modifiers.
[0014] Preferably, the specific surface area of the granulated blast furnace slag powder is 550-750m 2 / kg, the specific surface area of the fly ash is 800-1000m 2 / kg, the specific surface area of the ceramic powder is 650-850m 2 / kg.
[0015] By adopting the above technical solution and using three kinds of powders with different specific surface areas, the cementitious material has a better particle grading, the porosity of the cementitious material is reduced, and a dense structure and a self-tight stacking system of microscopic level are formed.
[0016] In the second aspect, the present application provides a method for preparing a mineral-based reservoir anti-seepage wall reinforcement curing agent using the following technical solution: A method for preparing a mineral-based reservoir anti-seepage wall reinforcement curing agent comprises the following steps: The raw materials are weighed according to the component proportions, and the cement, modified composite powder, polyacrylamide and sodium polyacrylate are stirred and mixed evenly to prepare an anti-seepage wall reinforcement curing agent.
[0017] By adopting the above technical scheme, the anti-seepage wall reinforcement curing agent prepared above, whether mixed with the solidified body by dry or wet method, can enable the solidified body to complete solidification in a shorter time, and improve the density and durability of the solidified body, effectively resist the erosion of harmful media, and extend the service life of the solidified body.
[0018] In the third aspect, the application of a mineral-based reservoir anti-seepage wall reinforcement and curing agent in soil solidification adopts the following technical solution: The invention discloses an application of a mineral-based reservoir anti-seepage wall reinforcement and curing agent in soil solidification. Based on the weight of the soil to be solidified, the dosage of the anti-seepage wall reinforcement and curing agent is 16%-20% of the solidified soil.
[0019] By adopting the above technical scheme, the optimal dosage of the anti-seepage wall reinforcement curing agent in this application is 16%-20%, which can quickly solidify in a short time, and improve the density and durability of the cured material, thereby ensuring the stability and durability of the reservoir anti-seepage wall.
[0020] In summary, the present application includes at least one of the following beneficial technical effects: In this application, the composite powder and cement are easy to form a flocculated structure after adding water. After modification, the composite powder is evenly dispersed in the cement and polymer system, and forms a good particle gradation with cement, effectively filling the pores, and the CSH gel generated later will further refine the capillary pores of the cement stone, improve the density of the cement, and then improve the strength and durability of the solid body, reduce water penetration, and extend the service life of the solid body. Among them, the alkoxy group in the aminosilane will generate active silanol after hydrolysis, and the silanol and the hydroxyl group on the surface of the composite powder will undergo a condensation reaction to form a chemical bond, and the amino group will react with fumaric acid to form a cross-linked structure. At the same time, fumaric acid and polyacrylamide produce staggered polymer molecules, which improves the curing performance of the curing agent. In addition, sodium polyacrylate absorbs a large amount of free water and stores it in molecular chain micro-units, which not only reduces the penetration of water in the solidified soil but also improves the density. DETAILED DESCRIPTION
[0021] The present application is further described in detail below in conjunction with embodiments.
[0022] Preparation Example Preparation Example 1 Preparation of modified composite powder: (1) 30 kg of granulated blast furnace slag powder (specific surface area 450 m 2 / kg), 6kg fly ash (specific surface area of 800m 2 / kg) and 15kg ceramic powder (specific surface area 550m 2 / kg) and then ball-milled for 2 h to obtain a composite powder, then added to a 30% by mass NaOH solution, stirred rapidly and fully dispersed for 1 h, filtered and dried to obtain a pretreated powder; (2) adding 6.2 kg of 3-aminopropyltriethoxysilane to N-methylpyrrolidone to obtain a modified liquid; fully dispersing the pretreated powder in N-methylpyrrolidone to obtain a suspension; introducing nitrogen to uniformly mix the modified liquid and the suspension, reacting under mechanical stirring at 60° C. for 2 h, filtering, washing with anhydrous ethanol, and drying to obtain a silanized powder; (3) 17.8 kg of fumaric acid was dissolved in an ethanol solution, and then the silanized powder was added to the fumaric acid solution, reacted at 75° C. under mechanical stirring for 3 h, washed twice with anhydrous ethanol, filtered and dried to obtain a modified composite powder.
[0023] Preparation Example 2 Preparation of modified composite powder: (1) 30 kg of granulated blast furnace slag powder (specific surface area 550 m 2 / kg), 9kg fly ash (specific surface area of 900m 2 / kg) and 18kg ceramic powder (specific surface area of 650m 2 / kg) and then ball-milled for 2.5 hours to obtain a composite powder, then added to a 30% by mass NaOH solution, stirred rapidly and fully dispersed for 1.5 hours, filtered and dried to obtain a pretreated powder; (2) adding 8.0 kg of N-2-aminoethyl-3-aminopropyltrimethoxysilane to N-methylpyrrolidone to obtain a modified liquid; fully dispersing the pretreated powder in N-methylpyrrolidone to obtain a suspension; introducing nitrogen to uniformly mix the modified liquid and the suspension, reacting under mechanical stirring at 65° C. for 3 h, filtering, washing with anhydrous ethanol, and drying to obtain a silanized powder; (3) 22.8 kg of fumaric acid was dissolved in an ethanol solution, and then the silanized powder was added to the fumaric acid solution, reacted at 80° C. under mechanical stirring for 4 h, washed with anhydrous ethanol for 3 times, filtered and dried to obtain a modified composite powder.
[0024] Preparation Example 3 Preparation of modified composite powder: (1) 30 kg of granulated blast furnace slag powder (specific surface area 650 m 2 / kg), 12kg fly ash (specific surface area 1000m 2 / kg) and 21kg ceramic powder (specific surface area of 750m 2 / kg) and then ball-milled for 3 hours to obtain a composite powder, then added to a 30% by mass NaOH solution, stirred rapidly and fully dispersed for 2 hours, filtered and dried to obtain a pretreated powder; (2) adding 10.0 kg of 3-diethylenetriaminopropyltrimethoxysilane to N-methylpyrrolidone to obtain a modified liquid; fully dispersing the pretreated powder in N-methylpyrrolidone to obtain a suspension; introducing nitrogen to uniformly mix the modified liquid and the suspension, reacting under mechanical stirring at 70° C. for 4 h, filtering, washing with anhydrous ethanol, and drying to obtain a silanized powder; (3) 28.4 kg of fumaric acid was dissolved in an ethanol solution, and then the silanized powder was added to the fumaric acid solution, reacted at 85° C. under mechanical stirring for 5 h, washed with anhydrous ethanol for 3 times, filtered and dried to obtain a modified composite powder.
[0025] Preparation Example 4 The difference between this preparation example and preparation example 2 is that the granulated blast furnace slag powder is replaced by an equal amount of phosphorus slag powder.
[0026] Preparation Example 5 The difference between this preparation example and preparation example 2 is that fly ash is not added.
[0027] Preparation Example 6 The difference between this preparation example and preparation example 2 is that N-2-aminoethyl-3-aminopropyltrimethoxysilane is replaced by an equal amount of 3-mercaptopropyltrimethoxysilane.
[0028] Preparation Example 7 The difference between this Preparation Example and Preparation Example 2 is that N-2-aminoethyl-3-aminopropyltrimethoxysilane is not added.
[0029] Preparation Example 8 The difference between this preparation example and preparation example 2 is that fumaric acid is replaced by an equal amount of cinnamic acid.
[0030] Preparation Example 9 The difference between this Preparation Example and Preparation Example 2 is that fumaric acid is not added. Example
[0031] Example 1 A mineral-based reservoir anti-seepage wall reinforcement curing agent comprises the following raw materials: 18kg cement (ordinary Portland cement with a strength of 42.5), 50kg modified composite powder (prepared in Preparation Example 1), 11kg polyacrylamide (Lanerqing CAS No.: 9003-05-8), and 3.5kg sodium polyacrylate (Shuangcheng CAS No.: 9003-04-7).
[0032] The raw materials are weighed according to the component proportions, and the cement, modified composite powder, polyacrylamide and sodium polyacrylate are stirred and mixed evenly to prepare an anti-seepage wall reinforcement curing agent.
[0033] Example 2 20kg cement (ordinary Portland cement with strength grade 42.5), 60kg modified composite powder (prepared in Preparation Example 2), 12kg polyacrylamide (Lanerqing CAS No.: 9003-05-8), 4.5kg sodium polyacrylate (Shuangcheng CAS No.: 9003-04-7).
[0034] The raw materials are weighed according to the component proportions, and the cement, modified composite powder, polyacrylamide and sodium polyacrylate are stirred and mixed evenly to prepare an anti-seepage wall reinforcement curing agent.
[0035] Example 3 22kg cement (ordinary Portland cement with strength grade 42.5), 65kg modified composite powder (prepared in Preparation Example 3), 13kg polyacrylamide (Lanerqing CAS No.: 9003-05-8), 5.5kg sodium polyacrylate (Shuangcheng CAS No.: 9003-04-7).
[0036] The raw materials are weighed according to the component proportions, and the cement, modified composite powder, polyacrylamide and sodium polyacrylate are stirred and mixed evenly to prepare an anti-seepage wall reinforcement curing agent.
[0037] Example 4 The difference between this embodiment and embodiment 2 is that the modified composite powder adopts the modified composite powder prepared in preparation example 4.
[0038] Example 5 The difference between this embodiment and embodiment 2 is that the modified composite powder adopts the modified composite powder prepared in preparation example 5.
[0039] Comparative Example Comparative Example 1 A mineral-based reservoir anti-seepage wall reinforcement and curing agent, which is different from Example 2 in that the modified composite powder adopts the modified composite powder prepared in Preparation Example 6.
[0040] Comparative Example 2 A mineral-based reservoir anti-seepage wall reinforcement and curing agent, which is different from Example 2 in that the modified composite powder adopts the modified composite powder prepared in Preparation Example 7.
[0041] Comparative Example 3 A mineral-based reservoir anti-seepage wall reinforcement and curing agent, which is different from Example 2 in that the modified composite powder adopts the modified composite powder prepared in Preparation Example 8.
[0042] Comparative Example 4 A mineral-based reservoir anti-seepage wall reinforcement curing agent, which is different from Example 2 in that the modified composite powder adopts the modified composite powder prepared in Preparation Example 9.
[0043] Comparative Example 5 A mineral-based reservoir anti-seepage wall reinforcement and curing agent, which differs from Example 2 in that an equal amount of granulated blast furnace slag powder is used instead of the modified composite powder.
[0044] Performance testing 1. Unconfined compression test: Mix the anti-seepage wall reinforcement curing agent in Examples 1-5 and Comparative Examples 1-5 with the solidified body (the dosage of the anti-seepage wall reinforcement curing agent is 16%-20% of the solidified body), add an appropriate amount of water to make the moisture content 45%, stir evenly and pour into a standard mold with a diameter of 5 cm and a height of 10 cm, vibrate and compact slightly, and then cure in a curing room at a temperature of 20 degrees and a relative humidity of 98% for 7 and 28 days, respectively, for testing. According to GB / T50123-2019 "Standard for Geotechnical Test Methods", the unconfined compressive strength of the samples in Examples 1-5 and Comparative Examples 1-5 was tested using a Y-II strain-controlled unconfined compression instrument, and the results are recorded in Table 1.
[0045] 2. Carbonation resistance test: The cut-off wall reinforcement curing agent in Examples 1-5 and Comparative Examples 1-5 was mixed with a solidified body (the amount of the cut-off wall reinforcement curing agent was 16%-20% of the solidified body), and a proper amount of water was added to make the moisture content 45%, and a test piece with a size of 100mm×100mm×400mm was made. After curing for 28 days, a carbonation resistance test was conducted. The test was conducted using a TH-074 concrete carbonization box. After 28 days of carbonization, the test piece was taken out and broken to determine the carbonization depth. The results are recorded in Table 1.
[0046] 3. Chloride ion penetration resistance test: The rapid test method for chloride ion migration (RCM) is used. The test refers to the chloride ion penetration resistance coefficient D in the "Standard for Long-term Performance and Durability Test Methods of Ordinary Concrete". RCM The test was conducted using specimens of ф100mm×50mm, with three specimens in a group, and one group of specimens was tested at each age. The arithmetic mean of the results of each group of three specimens was taken as the D RCM Measured value, unit 10 -12 m 2 / s. The results are recorded in Table 1.
[0047] 4. Salt freeze-thaw cycle resistance: refer to GB / T 50082-2009, use a rapid freeze-thaw tester to test, inject the prepared 5% Na2SO4 solution and 5% MgSO4 solution into the specimen box respectively, then put the test specimen into the specimen box, so that the specimen is about 2 cm away from the liquid surface, and each freeze-thaw cycle during the freeze-thaw cycle is completed within (2-4) h, and the thawing time shall not be less than 1 / 4 of the entire freeze-thaw time. The freezing temperature of the specimen is -15°C and the melting temperature is 10°C; when the test reaches the specified number of freeze-thaw cycles or the mass loss rate of the specimen reaches 5% or the strength loss rate of the specimen reaches 25%, stop the test, and record the mass loss rate and compressive strength of the specimen.
[0048] Table 1 According to Example 2, Examples 4-5, and Comparative Example 5 and in combination with the data in Table 1, it can be seen that the present application uses a compound of three powders, namely, granulated blast furnace slag powder, fly ash, and ceramic powder, to achieve a good curing effect. Compared with a single mineral powder, the composite powder of the present application can make up for the shortcomings of a single mineral powder, give play to the superposition effect of multiple materials, fill in the gaps between cement particles, reduce porosity, and form a denser structure, thereby improving the strength and durability of the cured body.
[0049] According to Example 2 and Comparative Example 1 and combined with the data in Table 1, it can be seen that the compressive strength and durability of the solidified body in Example 2 are significantly higher than those in Comparative Example 1, and the modification effect of aminosilane on the composite powder is due to mercaptosilane. Among them, aminosilane combines with the hydroxyl group on the surface of the composite powder through the silanol group, and the amine group reacts with the carboxyl group in the fumaric acid to undergo a dehydration reaction, so that aminosilane and fumaric acid are successfully coated on the surface of the composite powder as modifiers, so that the composite powder is evenly dispersed in the cement and polymer system, and filled in the pores of the solidified body, increasing the density of the solidified body, reducing the penetration of moisture and harmful media, and effectively improving the durability of the solidified body.
[0050] According to Example 2 and Comparative Example 2 and in combination with the data in Table 1, it can be seen that when the composite powder is modified, if aminosilane is not added, the modification effect is poor, the composite powder is prone to agglomeration, and the distribution is uneven in the cement and polymer system. On the contrary, by silanization modification of the composite powder with aminosilane, the agglomeration of the powder is reduced, the compatibility of the composite powder between cement and polymer materials is effectively increased, the composite powder is evenly dispersed in the composite material system, the stacking porosity of the powder is effectively reduced, and a high-density, low-permeability reinforcement layer is formed in the solidified soil.
[0051] According to Example 2 and Comparative Examples 3-4 and combined with the data in Table 1, it can be seen that the combination of aminosilane and fumaric acid has a good effect on the modification of the composite powder. Among them, the benzene ring contained in cinnamic acid has an adverse effect on the curing performance of the curing agent. Fumaric acid forms a cross-linked structure by reacting with amino groups. At the same time, fumaric acid and polyacrylamide produce staggered polymer molecules, which effectively improve the curing performance of the curing agent, making the internal structure of the cured body more compact, and carbon dioxide gas, harmful media, etc. are difficult to invade the interior of the cured body, and only react on the surface, effectively extending the service life of the cured body.
[0052] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed. However, as long as it is within the scope of the claims of the present application, it shall be protected by the patent law.
Claims
1. A mineral-based reservoir anti-seepage wall reinforcement curing agent, characterized in that: The invention is prepared from the following raw materials by weight: 18-22 parts of cement, 50-65 parts of modified composite powder, 11-13 parts of polyacrylamide, 3.5-5.5 parts of sodium polyacrylate; The raw materials for preparing the modified composite powder include composite powder, aminosilane and fumaric acid, and the weight ratio of the composite powder, aminosilane and fumaric acid is 10: (1.2-1.6): (3.5-4.5).
2. A mineral-based reservoir anti-seepage wall reinforcement and curing agent according to claim 1, characterized in that: The composite powder comprises granulated blast furnace slag powder, fly ash and ceramic powder, and the weight ratio of the granulated blast furnace slag powder, fly ash and ceramic powder is 1: (0.2-0.4): (0.5-0.7).
3. A mineral-based reservoir anti-seepage wall reinforcement and curing agent according to claim 2, characterized in that: The preparation method of the modified composite powder is: (1) Granulated blast furnace slag powder, fly ash and ceramic powder are mixed evenly and ball milled for 2-3 hours to obtain composite powder, and then the composite powder is added to NaOH solution, rapidly stirred and fully dispersed for 1-2 hours, filtered and dried to obtain pretreated powder; (2) adding aminosilane to the dispersant to obtain a modified liquid; Fully dispersing the pretreated powder in a dispersant to obtain a suspension; The modified liquid and the suspension were mixed evenly by introducing nitrogen, reacted for 2-4 hours under mechanical stirring at 60-70°C, filtered, washed and dried with anhydrous ethanol to obtain silanized powder; (3) Dissolve fumaric acid in an ethanol solution, then add the silanized powder to the fumaric acid solution, react for 3-5 hours under mechanical stirring at 75-85°C, wash with anhydrous ethanol 2-3 times, filter and dry to obtain a modified composite powder.
4. The mineral-based reservoir anti-seepage wall reinforcement and curing agent according to claim 3, characterized in that: The dispersant in step (2) is N-methylpyrrolidone.
5. The mineral-based reservoir anti-seepage wall reinforcement and curing agent according to claim 1, characterized in that: The aminosilane is one or more of 3-aminopropyltriethoxysilane, N-2-aminoethyl-3-aminopropyltrimethoxysilane, and 3-diethylenetriaminopropyltrimethoxysilane.
6. The mineral-based reservoir anti-seepage wall reinforcement and curing agent according to claim 2, characterized in that: The specific surface area of the granulated blast furnace slag powder is 450-650m 2 / kg, the specific surface area of the fly ash is 800-1000m 2 / kg, the specific surface area of the ceramic powder is 550-750m 2 / kg.
7. The method for preparing the mineral-based reservoir anti-seepage wall reinforcement and curing agent according to any one of claims 1 to 6, characterized in that: The following steps are involved: The raw materials are weighed according to the component proportions, and the cement, modified composite powder, polyacrylamide and sodium polyacrylate are stirred and mixed evenly to prepare an anti-seepage wall reinforcement curing agent.
8. Use of the mineral-based reservoir anti-seepage wall reinforcement and curing agent as described in any one of claims 1 to 6 in soil solidification.
9. The use according to claim 8, based on the weight of the soil to be solidified, the dosage of the cut-off wall reinforcement and curing agent is 16%-20% of the solidified soil.